Personal Data in Artificial Intelligence Systems: Natural Language Processing Technology - I. G. Ilin (Journal of Digital Technologies and Law, 2024)
Objective: to conceptualize, from the viewpoint of personal data protection legislation, the development of natural language processing technology, identifying possible legal barriers to such development and directions for further research of the issue.Methods: the research is based on general scientific methods of cognition, along with which formal-legal and comparative-legal methods were applied, as well as the method of theoretical modeling.Results: it was found that the observance of personal data regime natural language processing in the development of natural language processing technology leads technology, to a conflict between private-legal and public-legal interests, which, personal data in turn, creates obstacles for further development of this technology. The shortcomings of the existing legal order are shown, namely, the insufficient correspondence to the technical features of technology development. This may lead to the risks of excessive regulation, or, on the contrary, to the risks of neglecting critical areas that require protection. Problems in qualifying the data involved in the technology development are outlined. An attempt is made to define the limits of ensuring the lawfulness of personal data processing within the natural language processing technology. The material, temporal and territorial effect of the legal regulation in this field is identified as the limits of ensuring the legality. The author touches upon the possibility of using personal data as a consideration, which is important for the development of natural language processing technology and for the improvement of the information and communication technology industry.Scientific novelty: the paper supplements the scientific discussion on the legal regulation of personal data processing by artificial intelligence systems with an analysis of natural language processing technology. The latter is insufficiently studied, making it relevant to research information law, namely, the legal relations arising around artificial intelligence systems, and to assess the impact of a personal data regime on the development of natural language processing technology.Practical relevance: the applied aspects of the problems researched and the results obtained can be used to improve the legal regulation of public relations in the field of creation and development of artificial intelligence, as well as to identify and assess the legal risks arising in the personal data processing by developers of digital products based on natural language processing technology.